PENGARUH DISIPLIN KERJA, PEMBERIAN KOMPENSASI, DAN PENGEMBANGAN KARIR TERHADAP SEMANGAT KERJA KARYAWAN BAGIAN PRODUKSI PADA PT. LUTVINDO WIJAYA PERKASA PEKANBARU - Fany Veronica br Marpaung (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
This research was conducted at PT. Lutvindo Wijaya Perkasa Pekanbaru Riau Province to determine the effect of work discipline, compensation, and career development on the morale of employees in the production department at PT. Lutvindo Wijaya Perkasa Pekanbaru. The purpose of this study is to find out and analyze the effect of the independent variables, namely work discipline, compensation, and career development on the dependent variable, namely the morale of employees in the production department at PT. Lutvindo Wijaya Perkasa Pekanbaru. This study used a descriptive quantitative research methodology to analyze the data collected by distributing questionnaires to 55 respondents using a simple random sampling altalu bialsal data collection technique called the simple alcalk technique. The results of the study are that there is a positive and significant effect of work discipline, compensation, and career development on the morale of employees in the production department at PT. Lutvindo Wijaya Perkasa Pekanbaru.